Pengaruh Perkembangan Teknologi Pertanian terhadap Tingkat Kemiskinan Petani di NTT - Gawe, Maria Stevania Nati; Taolin, Margaretha Gramediana; Tulasi, Floresita Melin; Lian, Yohanes Pemandi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Poverty in the agricultural sector remains an unresolved issue. Despite various efforts to address it, no effective solution has been found. This research aims to examine the impact of technological developments on the poverty levels of farmers in the NTT province. A qualitative research method was employed, utilizing interviews to gather accurate data from farmer groups in NTT. The findings indicate that agricultural technology plays a significant role in increasing farmers' income and reducing poverty in the region. However, to achieve optimal results, it is essential to focus on costs, improve access to information, and enhance infrastructure that supports technology, ensuring that more farmers in NTT can benefit from it